Counsellor Ideal Character Based on Javanese Cultural Values - Habsy, Bakhrudin All; Mariani Binti Md Nor (International Journal of Multicultural Counseling and Development, 2024)
When dealing with other people, especially counsellors, counsellors must be able to be ngemong by showing a tolerant attitude, not reproaching, not demanding and helping them in fulfilling their needs. by showing a ngemong attitude, the counsellor will show himself as a trustworthy and compassionate person. Of course, professional counsellors have at least reached the level of "tepa sarira" where the counsellor is able to understand what others feel. In order not to become "The wounded healer", a counsellor needs to be "introspective" where he tries to understand his own situation as honestly as possible. However, it would be even better if the counsellor is able to determine his/her identity as a person (mulat sarira). Thus, a counsellor can carry out his role as a professional person with selflessness for the good of many people and as a divine person. As a person born in Java, a Javanese counsellor should instil the values of Javanese cultural wisdom in his/her life while remaining flexible and open to the times. So, in addition to staying updated with the outside world, the counsellor is also a successor to the noble values of the nation.